2005
DOI: 10.1159/000084819
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Series of Long-Term Survivors of Metastatic Breast Cancer in Complete Remission

Abstract: Aim: To describe clinical features, treatment modalities and long-term outcome of patients with overt metastatic breast cancer in complete remission for more than 5 years. Patients and Methods: A retrospective survey of 12 patients who were referred to a single institution from 1982 to 1995. Results: The majority of the long-term survivors had a good performance status, endocrine-responsive disease and a single metastatic site. Ten patients had received chemotherapy, 8 patients hormone therapy, and 2 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In our series, a significant correlation between the achievement of objectives response and subsequent PCB has been found, as previously showed in other retrospective analyses mainly conducted in metastatic breast cancer patients treated with high-dose chemotherapy and autologous hematopoietic stem cell support [28,29]. We also found a correlation between the number of previous treatments for advanced disease and probability of PCB.…”
Section: Discussionsupporting
confidence: 89%
“…In our series, a significant correlation between the achievement of objectives response and subsequent PCB has been found, as previously showed in other retrospective analyses mainly conducted in metastatic breast cancer patients treated with high-dose chemotherapy and autologous hematopoietic stem cell support [28,29]. We also found a correlation between the number of previous treatments for advanced disease and probability of PCB.…”
Section: Discussionsupporting
confidence: 89%
“…Although the majority of patients with MBC treated with trastuzumab-based regimens progress within one year [ 5 , 8 ], few patients experience prolonged remission [ 9 , 10 ]. Limited data have been published on long term remission under treatment with trastuzumab and are usually based on case reports or small patient numbers [ 11 13 ]. Aspects such as clinical predictive factors of long-term response to trastuzumab or the optimal duration of trastuzumab therapy in MBC patients achieving stable response remain to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…The median survival was 42 months (range: 4–254 months) in 16.6% of patients who achieved CR after treatment with doxorubicin‐based combined chemotherapy and 3.1% of those remained disease free for more than 5 years. A retrospective series of long‐term survivors of MBC demonstrated that ER‐positive disease, ≤3 sites involved, good performance status, and previous exposure to anthracyclines were associated with increased CR rates (13,14). At a follow‐up of 11.7 years, 11 of 12 patients (91.7%) were still alive (14).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective series of long‐term survivors of MBC demonstrated that ER‐positive disease, ≤3 sites involved, good performance status, and previous exposure to anthracyclines were associated with increased CR rates (13,14). At a follow‐up of 11.7 years, 11 of 12 patients (91.7%) were still alive (14). A more recent article reviewed 135 MBC patients treated between 1992 and 2008 and evaluated tumor/disease factors as possible survival predictors (13).…”
Section: Discussionmentioning
confidence: 99%